2015
DOI: 10.1111/bcp.12669
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide in the joint: contributions to pain and inflammation

Abstract: Arthritis is the commonest cause of disabling chronic pain, and both osteoarthritis (OA) and rheumatoid arthritis (RA) remain major burdens on both individuals and society. Peripheral release of calcitonin gene-related peptide (CGRP) contributes to the vasodilation of acute neurogenic inflammation. Contributions of CGRP to the pain and inflammation of chronic arthritis, however, are only recently being elucidated. Animal models of arthritis are revealing the molecular and pathophysiological events that accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 125 publications
4
73
3
2
Order By: Relevance
“…The authors postulated a molecular link between these two conditions in the form of Calcitonin gene-related peptide "CGRP" which is released during migraine attacks and is potentially also involved in the pathogenesis of abdominal pain by causing inflammation of sensory GI neurons. Additionally, our results recovered relationship between migraine and joint pains, this could be interpreted in the light of the CGRP induced synovitis, where it was found that CGRP contributes to transition from normal to persistent synovitis, and the progression from nociception to sensitization [39]. Also, CGRP may play a role in pain transmission in somatic pain conditions such as joint and muscular chronic pain [40].…”
Section: Discussionsupporting
confidence: 70%
“…The authors postulated a molecular link between these two conditions in the form of Calcitonin gene-related peptide "CGRP" which is released during migraine attacks and is potentially also involved in the pathogenesis of abdominal pain by causing inflammation of sensory GI neurons. Additionally, our results recovered relationship between migraine and joint pains, this could be interpreted in the light of the CGRP induced synovitis, where it was found that CGRP contributes to transition from normal to persistent synovitis, and the progression from nociception to sensitization [39]. Also, CGRP may play a role in pain transmission in somatic pain conditions such as joint and muscular chronic pain [40].…”
Section: Discussionsupporting
confidence: 70%
“…Recent reviews have focused on the role of cytokines, neuropeptides, and cannabinoids in the development of peripheral sensitization in OA (38, 45, 46). Therefore, here we will focus on describing the potential role of NGF, sodium channels, and non-neuronal cells to peripheral sensitization in OA.…”
Section: Peripheral Sensitizationmentioning
confidence: 99%
“…Хроническая боль может быть следствием острой боли, обусловленной неадекватным процессом репарации, если вновь синтезированная функциональная ткань отличается по своему клеточному и матриксному составу от той, что предшествовала повреждению [53]. Другой тип хронической боли включает разобщение процессов генерации болевого сигнала и начального повреждения ткани (нейропатическая боль) [54].…”
Section: классификация видов боли при раunclassified
“…Хроническое воспаление при РА приводит не только к фокальным эрозиям кости внутри воспаленных суставов, но и к генерализованному остеопорозу в аксиальном и апендикулярном скелете [108]. Кроме того, в отличие от острой фазы, хроническое воспаление часто связано с генерацией специфического иммунного ответа с одновременным повреждением ткани [53]. При этом, повреждение может прогрессировать, несмотря на отсутствие клинической активности (немое прогрессирование) [109] вследствие низкой чувствительности клинических методов оценки воспаления сустава, субклинического синовита или системных эффектов, вызванных активными процессами в других суставах [110].…”
Section: ассоциация разрушения суставов с повышением экспрессии протеunclassified